Recurrent ‘Occult’ 18F-FDG Uptake in an Atypical Case of Anti-Myeloperoxidase Antineutrophil Cytoplasmic Antibody-Associated Vasculitis - Amélie Castiaux; Irina Vierasu; Frederic Vandergheynst; Serge Goldman (European Journal of Case Reports in Internal Medicine, 2022)
A 72-year-old woman, with anti-myeloperoxidase antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV), presented with two episodes of spinal pachymeningitis (at two different levels 9 years apart, cervical in 2011 and dorso-lumbar in 2020) associated with aortitis and only demonstrated by F-18 fluorodeoxyglucose positron emission tomography/computed tomography (18F-FDG PET/CT). This association between aortitis and pachymeningitis in AAV appears exceptional. Moreover, the relapse of aortitis and pachymeningitis in 2020 was not accompanied by an increase in ANCA. This case demonstrates the value of 18F-FDG PET/CT in the management of AAV, providing evidence of the recurrence and distribution of lesions in various organs, including those with unexpected involvement.